A NAA collaborative study in white rice performed in seven Asian countries - J. H., Moon; M., Ebihara; B. F., Ni; B., Arporn; P., Setyo; R. M., Theresia; B. S., Wee (Springer, 2011)
Since 2000, collaborative studies for applying NAA have been performed through the Forum for Nuclear Cooperation in Asia (FNCA) sponsored by the Japanese Government. White rice is a main food for Asians and thus was selected as a common target sample for a collaborative study in 2008. Seven Asian countries including China, Indonesia, Japan, Korea, Malaysia, Philippines and Thailand, are greatly concerned about the composition of arsenic, heavy metals, and essential trace elements and took part in this study. Rice samples were purchased and prepared by following a protocol that had been proposed for this study. Samples were analyzed by their own NAA systems. In each country, more than 10 elements were examined and the results were compared. These data will be very useful in the monitoring of the levels of food contamination and to evaluate the nutritional status for people living in Asia.